Evolutionary Path and Influences on Marine Ecological Farming: Dual Perspective of Government Intervention and Enterprise Participation - Qun Zhang; Junjie Lin; Wenyue Wei; Yuanzhu Wei (Discrete Dynamics in Nature and Society)
Marine ecological aquaculture is considered a robust scientific farming model, but it has not been widely promoted in China. Although some studies have examined stakeholders’ interests in ecological transformation, few studies to date have analyzed the interaction mechanism of the stakeholders in ecological transformation. Therefore, drawing on evolutionary game theory, this study analyzed the different behavioral strategies and evolutionary mechanisms of the government, marine aquaculture farmers, and aquatic enterprises engaged in marine farming processes. Furthermore, a numerical simulation was conducted to evaluate the rationality of the theoretical model. The results show that several factors affected the ecological transformation of mariculture. Government subsidies reduced farmers’ and aquatic enterprises’ costs of adopting ecological farming. The government’s increasing fines for aquaculture pollution slowed down the speed of the system to a stable point. The cost of adopting ecological farming by farmers and aquatic enterprises will affect their decision to adopt or invest in it. The increase in the market price of eco-aquatic products helped accelerate the ecological transformation of mariculture. The brand effect obtained by aquatic enterprises by investing in ecological farming helped increase participation to further improve this practice. In terms of policy implications, we recommend the promotion and guidance of marine aquaculture technology, government support and investment, environmental control of the aquaculture industry, and brand building of eco-aquatic products to transform and upgrade marine aquaculture farming.